Pemanfaatan Publikasi Di Media Sosial Untuk Lembaga Pendidikan - Fitri Amilia; Gitta Rowindi; Syahrul Mubaroq (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of the article is to describe the use of social media as a publication media in and for educational institutions. This publication is to provide information that is easily accessible by all levels of society. The provision and dissemination can be done on various social media. Social media is a media platform that focuses on the existence of users which facilitates them in their activities and collaboration. The development of social media publications is utilized by various institutions, including educational institutions. Social media publications play an important role in disseminating institutional information, institutional excellence, institutional curriculum, and so on. Based on these needs, this community service was carried out at Pondok Modern Muhammadiyah Pakusari to meet their needs in developing publications on social media. So far, the publications on social media that have been carried out are still limited. Through this community service activity, it is hoped that there will be new skills in managing publications on social media for the dissemination of institutional information. This publication will also be an efficient and effective promotional media. The activity is carried out with a workshop pattern, starting with the provision of materials, guided practice, hands-on practice, and evaluation of activities. To make the activity material easy to understand, the community service implementation team has provided an activity module, so that it can be read after the activity. Based on the activity, five recommendations for social media that are suitable for use in institutional publications are given, namely Facebook, youtube, website, Instagram, and TikTok. The Muhammadiyah Pakusari Islamic Boarding School has a Facebook page and also a page, website, and youtube. Instagram and TikTok will be developed after this activity.